PRACTICING ACTIVITIES TO DEVELOP COMPONENTS OF MATHEMATICAL THINKING COMPETENCY IN ECONOMICS FOR ECONOMICS MAJOR STUDENTS - Thai Thi Van Anh*; Dao Tam (Tạp chí Khoa học)
In this paper, we study and propose the concept of mathematical thinking competency in economics for economics major students. Firstly, the paper focuses on clarifying the theoretical foundations of knowledge and mathematical thinking in the economic context and analyzing the applications of mathematical thinking in economic activities. Next, we review relevant studies on fostering mathematical thinking competency in economics, identifying key factors for designing an appropriate mathematics learning environment for economics students. By designing learning activities, students can experience and solve real- world problems, thereby developing components of mathematical thinking competency in economics. Thus, the paper raises the issue of constructing a suitable learning environment that enables students to engage in activities aligned with the components of mathematical thinking competency in economics, thereby enhancing training quality and the application of mathematics in economics.